Pengembangan Sistem Informasi Manajemen untuk Meningkatkan Kualitas Pengelolaan Data serta Efektivitas Layanan Guru Bimbingan dan Konseling di SMA “XYZ” Surabaya - Kartika Indrasari (Ilmiah Manajemen Bisnis, 2019)
Abstract — This study describes the development of a guidance and counseling management information system (MIS) at “XYZ” High School, Surabaya to fulfll the need to manage students data in a quick and accurate way to improve the effectiveness of guidance and counseling services delivered by the teachers. This MIS is a webbased application in which the application can be accessed through a web browser using the internet and intranet networks. 92,3% students and 85,7% teachers prefer to use this MIS since MIS provides various benefts, such as: students can access information about themselves in order to develop and improve their studies as well as their further studies; guidance and counseling teachers can have meaningful information based on student data sets to conduct more targeted counseling processes; others teachers can design teaching and learning methods, the seating to help students socialize, improve and develop their spiritual intelligence; schools can evaluate the outputs to improve and develop the curriculum, teaching and learning processes and school systems. Considering the Association of “XYZ” Surabaya, the MIS should be developed further to ensure the meaningful and sustainability of guidance and counseling service for the students during the period of study. Keywords — management information system, management of data, effectiveness of services